Component cell–based restriction of spectral conditions and the impact on CPV module power rating. (26th January 2018) - Steiner, Marc; Muller, Matt; Siefer, Gerald; Bett, Andreas W.
Abstract: One approach to consider the prevailing spectral conditions when performing CPV module power ratings according to the standard IEC 62670‐3 is based on spectral matching ratios (SMRs) determined by the means of component cell sensors. In this work, an uncertainty analysis of the SMR approach is performed based on a dataset of spectral irradiances created with SMARTS2. Using these illumination spectra, the respective efficiencies of multijunction solar cells with different cell architectures are calculated. These efficiencies were used to analyze the influence of different component cell sensors and SMR filtering methods. The 3 main findings of this work are as follows. First, component cells based on the lattice‐matched triple‐junction (LM3J) cell are suitable for restricting spectral conditions and are qualified for the standardized power rating of CPV modules—even if the CPV module is using multijunction cells other than LM3J. Second, a filtering of all 3 SMRs with ±3.0% of unity results in the worst case scenario in an underestimation of −1.7% and overestimation of +2.4% compared to AM1.5d efficiency. Third, there is no benefit in matching the component cells to the module cell in respect to the measurement uncertainty. Abstract : In this work, an uncertainty analysis of IEC 62670‐3 power ratings based on spectral matching ratio based power rating is performed using a dataset of spectral irradiances created with SMARTS2. The 2 main findings of this work are as follows. First, component cells based on the lattice matched triple junction cell are suitable for restricting spectral conditions and are qualified for the standardized power rating of CPV modules. Second, a filtering of all 3 SMRs with ±3.0% of unity results in the worst case scenario in an underestimation of 1.7% and overestimation of +2.4% compared to AM1.5d efficiency.